Teachers’ individual and collective efficacy in relation to their attitudes towards inclusion –Analyses from an international study comprising Canada, Germany & Switzerland. - Knickenberg, Margarita; Kullmann, Harry; Wüthrich, Sergej; Sahli Lozano, Caroline

Examining aspects of students’ current academic motivation in relation to peer interactions and social environment in the classroom using the Experience sampling method. - Knickenberg, Margarita; Zurbriggen, Carmen

Effects of peer interactions and the social environment on students’ current academic motivation in the classroom: An experience sampling study. - Knickenberg, Margarita; Zurbriggen, Carmen

Du Châtelet, Induction, and Newton’s Rules for Reasoning - Wells, Aaron (European Journal of Philosophy)
I examine Du Châtelet’s methodology for physics and metaphysics through the lens of her engagement with Newton’s Rules for Reasoning in Natural Philosophy. I first show that her early manuscript writings discuss and endorse these Rules. Then, I argue that her famous published account of hypotheses continues to invoke close analogues of Rules 3 and 4, despite various developments in her position. Once relevant experimental evidence and some basic constraints are met, it is legitimate to inductively generalize from observations; general hypotheses can thereafter be assumed as true until contrary experiments show otherwise. I conclude by arguing that this account of induction plays an essential role in her metaphysics, both in an argument for simple substances—which has an inductive premise—and in her attempt to distinguish acceptable and unacceptable metaphysical commitments.

The Principle of Sufficient Reason in Early Modern Philosophy of Science: Leibniz, Du Châtelet, and Euler - Wells, Aaron (The Principle of Sufficient Reason: A History)
I distinsuish three ways in which early modern rationalists seek to apply the principle to empirical science. Previous readings have neglected how these thinkers assume substantive theories of explanation and intelligibility in many of their deployments of this rationalist principle. I argue that Leibniz, Du Châtelet, and Euler are all vulnerable to the objection that they deploy their standards of intelligibility inconsistently: their own favored explanations do not always live up to the standard. This chapter also defends more particular interpretive claims about these thinkers, for example arguing against Jeff McDonough’s anti-realist reading of Leibniz on laws of nature.

Women in Early Modern Science: Du Châtelet, Bassi, and Agnesi - Wells, Aaron (The History and Philosophy of Science, 1450 to 1750)

Du Châtelet’s Philosophy of Mathematics - Wells, Aaron (The Bloomsbury Companion to Du Châtelet)

Fast model-based calibration of multiple injections for a CI engine using nonlinear optimal control - Moretto, Giordano; Schnell, Nicolas; Frey, Jonathan; Karakaya, Yasin; Amstutz, Alois; Diehl, Moritz; Kasper, Tina; Onder, Christopher (Control Engineering Practice)

Gottes Treue zu Israel (Röm 9–11) - Taschl-Erber, Andrea; Woppowa, Jan (Elementare Bibeltexte)

Manipulating spectral topology and exceptional points by nonlinearity in non-Hermitian polariton systems - Wingenbach, Jan; Schumacher, Stefan; Ma, Xuekai (Physical Review Research, in press)

Die Kriterien und Zusammensetzung der EU-Blacklist als Grundlage des Steueroasen-Abwehrgesetzes – Eine kritische Würdigung - Schön, Lena; Graßl, Benjamin; Giese, Henning (Steuer und Wirtschaft)

Persis - Breuer, Saskia Rebecca (Encyclopedia of the Bible and its Reception (EBR))

Effect of DNA Origami Nanostructures on Bacterial Growth - Garcia-Diosa, Jaime Andres; Grundmeier, Guido; Keller, Adrian (ChemBioChem)
DNA origami nanostructures are a powerful tool in biomedicine and can be used to combat drug‐resistant bacterial infections. However, the effect of unmodified DNA origami nanostructures on bacteria is yet to be elucidated. With the aim to obtain a better understanding of this phenomenon, the effect of three DNA origami shapes, i.e., DNA origami triangles, six‐helix bundles (6HBs), and 24‐helix bundles (24HBs), on the growth of Gram‐negative Escherichia coli and Gram‐positive Bacillus subtilis is investigated. These results reveal that while triangles and 24HBs can be used as a source of nutrients by E. coli and thereby promote population growth, their effect is much smaller than that of genomic single‐ and double‐stranded DNA. However, no effect on E. coli population growth is observed for the 6HBs. On the other hand, B. subtilis does not show any significant changes in population growth when cultured with the different DNA origami shapes or genomic DNA. The detailed effect of DNA origami nanostructures on bacterial growth thus depends on the competence signals and uptake mechanism of each bacterial species, as well as the DNA origami shape. This should be considered in the development of antimicrobial DNA origami nanostructures.
Keywords: Organic Chemistry; Molecular Biology; Molecular Medicine; Biochemistry

Photochemical Reaction Enabling the Engineering of Photonic Spin−Orbit Coupling in Organic-Crystal Optical Microcavities - Liang, Qian; Ma, Xuekai; Gu, Chunling; Ren, Jiahuan; An, Cunbin; Fu, Hongbing; Schumacher, Stefan; Liao, Qing (Journal of the American Chemical Society (JACS))

Special Section/Schwerpunkt: Poetologien mehrdeutigen Erinnerns. Historisierungsstrategien in der deutschsprachigen Gegenwartsliteratur (andererseits. Yearbook of Transatlantic German Studies 11/12 (2022/23))

Poetologien mehrdeutigen Erinnerns in der deutschsprachigen Gegenwartsliteratur. - Eke, Norbert (andererseits. Yearbook of Transatlantic German Studies 11/12 (2022/23))

Maghemite nanoparticles synthesis via spray flame synthesis and particle characterization by hole in a tube sampling and scanning mobility particle sizing (HIAT-SMPS) (Applications in Energy and Combustion Science)
In order to standardize spray flame synthesis (SFS) studies, intensive work has been done in recent years on the design of burner types. Thus, in 2019, the so-called SpraySyn1 burner was introduced (SS1), which was subsequently characterized in numerical and experimental studies. Based on this research, a modification of the nozzle design was proposed, which has now been considered in the successor model, SpraySyn2 (SS2). As little is known about the effect of the nozzle adaptation on the particle formation, we operated both burners under identical operating conditions to produce maghemite. The final powder comparison showed that SS2 yielded considerable higher specific surface areas (associated with smaller primary particle sizes), lower polydispersity, and higher phase purity. To obtain further information on the size distributions of aggregates and agglomerates generated by SS2, aerosol samples were extracted by hole in a tube (HIAT) sampling and characterized by scanning mobility particle sizing (SMPS). Samples were extracted along the centerline at different heights above the burner (HAB) above the visible flame tip (>7 cm), and quenching experiments were performed to extract the aerosol samples at different dilution rates. Thereby, it was demonstrated that performing detailed quenching experiments is crucial for obtaining representative HIAT-SMPS data. In particular, agglomerates/aggregate sizes were overestimated by up to ~70 % if samples were not sufficiently diluted. If sufficient dilution was applied, distribution widths and mean particle mobility diameters were determined with high accuracy (sample standard derivation <5 %). Our data suggested the evolution of primary particle sizes was mostly completed <7 cm HAB and it was shown aggregates/agglomerates present above the visible flame were compact in structure (non- fractal). The mean diameter of the particle ensemble grew along the centerline from 6.9 nm (7 cm) to 11.4 nm (15 cm), while distribution widths grew from 1.42 to 1.52.
Keywords: Flame Spray Pyrolysis; SpraySyn2; Spray flame synthesis; Maghemite nanoparticles; Gas to particle-conversion; Hole in a tube sampling

„Es nimmt der Raum gastfreundlich auf die Menge“. Theodor Hells Prolog zur Eröffnung des Dresdner Hoftheaters (1841) - Eke, Norbert Otto (Die Kunst der Theatereröffnung. Ästhetik und Sozialgeschichte von Bühnenprologen)

„Wenn die Heilige Zeit da ist, werde ich […] weggehen“. Heilige Zeit in Claudia Llosas Madeinusa - Eke, Norbert Otto ((Un)verfügbar – Kulturen des Heiligen)

Das Heilige – Versuch einer Definition - Eke, Norbert Otto ((Un)verfügbar – Kulturen des Heiligen)